Metro Manila My city, my home, impact of colonization, primacy of Metro Manila, urban planning and development in the face of politics - Von Einsiedel, Nathaniel author; Casanova, Lilia C.G. editor; Luchi T. Rosales editor (Makati City, Metro Manila Alliance for Safe, Sustainable, and Resilient Environments (ASSURE, Inc.), 2019)
This book tells the story of how Manila developed from a vibrant, coastal village to a global mercantile trading center from the days of the Spanish Galleons to the cosmopolitan capital it is today.

It includes the author’s experiences with the planning and management of Metro Manila, from before its creation as a metropolitan region, through its evolution from the former MMC to the present MMDA.

It is a story of passion, dreams and hopes for Metro Manila of the author – the former Metro Manila Commissioner for Planning.
Contents: Chapter one: Introduction. -- Chapter two: Rebuilding Metro Manila after the war. -- Chapter three: The human settlements movement.-- Chapter four: The golden years of metropolitan planning. -- Chapter five: The changing of the guards (1984-2004). -- Chapter six: A glimmer of hope. -- Chapter seven: The Metro Manila I want.
Includes bibliographical references (pages 332-336).
AIT-4109G donated by Ivan Anthony S. Henares, Asian Institute of Tourism, University of the Philippines.
Keywords: Metropolitan areas -- Planning -- Philippines; Urban ecology -- Philippines -- Metro Manila; Urban policy -- Philippines -- Metro Manila; Cities and towns -- Growth; Manila Metropolitan Area (Philippines) -- Planning